Analisis Kesalahan Berbahasa Tataran Sintaksis dalam Skripsi Mahasiswa Universitas Islam Riau - Saputra, Mulyadi; Alber, Alber (Jurnal Sastra Indonesia, 2021)
A thesis written by students of the Islamic University of Riau, especially the Indonesian Language and Literature Education Study Program, still contains language errors, even though these students have gained in-depth knowledge and knowledge related to language, both oral and written. These errors occur at the syntactic level, especially the use of the phrase and sentence fields. Based on this, the purpose of this study is to describe the syntactic errors contained in the thesis of students of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Islamic University of Riau. This study uses the content analysis method with data collection techniques in the form of reading and recording techniques and data analysis techniques through data identification, data classification, data analysis, and concluding research results. The data source in this study is the thesis of students of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Islamic University of Riau who graduated in the first period of 2021. Based on the results and discussion, there are several language errors at the syntactic level in the phrase and sentence fields. Language errors in the phrase field include errors in using inappropriate prepositions, incorrect wording, excessive use of elements, and excessive use of superlatives. Meanwhile, the errors in the sentence fields include unsubjected sentences, unsubjected and unpredicated sentences, unnecessary use of question words, illogical sentences, and inserted between subjects and predicates.